Verset teen mag: Die pelgrim se reis in drie "Sondergut" gelykenisse in Lukas 15 en 16 - Aarde, Andries van (HTS teologiese studies, 2012)
Resistance against power: The pilgrim’s journey in three Sondergut parables in Luke 15 and 16. The aim of this essay is to explain the philosophical viewpoints of Michel Foucault concerning the power of knowledge and its consequences when individuals are subjectified into ‘docile bodies’. According to this perspective, resistance against power commences when the little stories of individuals are told in opposition to the master narratives of ideologies of power. The essay refers to Steve Biko and Martin Luther King whose stories of resistance against racism as an ideology of power serve as examples. Their examples of resistance are hermeneutically and heuristically applied to the interpretation of the parables in Luke 15 and 16. These parables are peculiar to Luke’s theology. The essay exposes the subjectifying of the identities of the ‘lost son’ and ‘father’, the ‘master’ and ‘steward’, and the ‘rich man’ and the ‘poor man’, as these heteronormative categories occur in parabolic stories in Luke 15 and 16. The essay concludes with a vision for Christians today on how to recognise power relationships and how to respond in a non-violent way to the dominant ideologies promoting power.